TAX INCENTIVES ON TAX COMPLIANCE ON MICRO SMALL MEDIUM ENTERPRISES DURING THE COVID-19 PANDEMIC (Survey at the Department of Cooperatives, Micro, Small and Medium Enterprises in Bandung) - Sari, Diana; Simanjuntak, Natalya; Syafira, Fitri; Jihana, Risma; Putri, Nur Alifa Fiani; Hidayatullah, Fikri (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study examines the application of tax incentives to micro, small and medium enterprises taxpayer compliance during the COVID-19 pandemic. Micro, small and medium enterprises medium taxpayers in Indonesia are given tax incentives by the government. The purpose of this study is to determine the existence of compliance in paying and declaring taxes during the pandemic. The COVID-19 pandemic factor affects the economic process, especially in the micro, small and medium sector. This research is in the form of research with the latest topics and is intended for micro, small and medium actors in the city of Bandung. Respondents amounted to 98 people. Although this study uses a small sample of micro, small and medium enterprises actors, the results cannot be concluded in general terms. The results of the study stated that the tax intensive enough to have an influence on the compliance of micro, micro, small and medium enterprises taxpayers.